Sleep disturbances correlate with behavioral problems among individuals with Wiedemann-Steiner syndrome - Ng, Rowena; Bjornsson, Hans Tomas; Fahrner, Jill A.; Harris, Jacqueline (Frontiers in Genetics, 2022)
Wiedemann-Steiner syndrome (WSS) is a rare genetic disorder caused by mutation in KMT2A and characterized by neurodevelopmental delay. This study is the first prospective investigation to examine the sleep and behavioral phenotypes among those with WSS through parent-informant screening inventories. A total of 24 parents of children/adults with WSS (11F, Mean age = 12.71 years, SD = 8.17) completed the Strengths and Difficulties Questionnaire (SDQ) and 22 of these caregivers also completed the Modified Simonds and Parraga Sleep Questionnaire (MSPSQ). On average, the majority of those with WSS (83%) were rated to show borderline to clinical level of behavioral difficulties on the SDQ. Approximately 83% were rated in these ranges for hyperactivity, 63% for emotional problems, and 50% for conduct problems. When applying prior published clinical cut-off for risk of sleep disturbance among those with neurodevelopmental disorders, over 80% of our sample exceeded this limit on the MSPSQ. Largely, caregivers’ ratings suggested restless sleep, rigid bedtime rituals, sleep reluctance and breathing through the mouth in sleep were most consistent problems observed. Partial correlations between sleep and behavioral domains showed elevated emotional problems were associated with parasomnia characteristics after controlling for age. Daytime drowsiness and activity were associated with more hyperactivity. Those with more night waking problems and delayed sleep onset were rated to show more severe conduct problems. Overall, these findings suggest dysfunctional sleep behaviors, hyperactivity, and affective problems are part of the neurobehavioral phenotype of WSS. Routine clinical care for those affected by WSS should include close monitoring of sleep and overactive behaviors.